2018
DOI: 10.1080/19382014.2017.1405202
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of islet cryopreservation

Abstract: Pancreatic islet transplantation is being extensively researched as an alternative treatment for type 1 diabetic patients. This treatment is currently limited by temporal mismatch, between the availability of pancreas and isolated islets from deceased organ donor, and the recipient's need for freshly isolated islets. To solve this issue, cryopreservation of islets may offer the potential to bank islets for transplant on demand. Cryopreservation, however, introduces an overwhelmingly harsh environment to the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…In addition, cell-based therapy does not prevent the possibility of whole-organ transplantation later. However, using mature cells for this therapy is limited due to the inability of these cells to proliferate in vitro, due to the metabolic damages induced by cryopreservation and to organ shortage as well [27,28,29].…”
Section: Cell-based Therapymentioning
confidence: 99%
“…In addition, cell-based therapy does not prevent the possibility of whole-organ transplantation later. However, using mature cells for this therapy is limited due to the inability of these cells to proliferate in vitro, due to the metabolic damages induced by cryopreservation and to organ shortage as well [27,28,29].…”
Section: Cell-based Therapymentioning
confidence: 99%
“…Since β cells are easier available and capable of secreting insulin, their encapsulation in hydrogel could thus mimic real islet to regulate blood glucose. Different from the traditional islet cryopreservation methods including a high concentration of permeable cryoprotectants (pCPAs, like dimethyl sulfoxide, glycerol, ethylene glycol and propylene glycol) to prevent ice crystal damages, recent preservation methods enable efficient storage of various cells with hydrogel encapsulation, electromagnetic fields, nanoparticles, etc . Researches have been carried out and showed that by using droplet microfluidics numerous functional materials based on hydrogels could be fabricated .…”
Section: Introductionmentioning
confidence: 99%
“…The cryopreservation of stem cells and embryos has been successful (10,11). The cryopreservation of rat testicular tissue (12), rat, pig and human islet tissue (13)(14)(15)(16) and liver tissues of mice, rats, dogs, monkeys and humans has also been successful (17). Cryopreservation is not only conducive to the accumulation of donor tissue, but also significantly reduces its immunity (18).…”
Section: Discussionmentioning
confidence: 99%